Character Education Strategies in Indonesian Language Instruction for Fostering Politeness and Discipline in Elementary Schools - Amalia Oktaviyani Fikamulyana; Dian Hidayati; Muhammad Zuhaery (Sakura Digital Nusantara, 2026)
Character education plays a vital role in fostering politeness and discipline among elementary school students. Indonesian Language instruction provides a strategic context for character development because language use reflects students' attitudes, discipline, and social behavior. This study aimed to describe the strategies of a character education program implemented through Indonesian Language instruction to foster politeness and discipline in an elementary school. A qualitative case study was conducted at SD Muhammadiyah Kadisoka, Yogyakarta, Indonesia, over a four-month period. The participants consisted of one principal, one vice principal for curriculum affairs, one fifth-grade Indonesian Language teacher, and one purposively selected fifth-grade student who participated in the interviews. Data were collected through interviews, classroom observations involving fifth-grade students, and document analysis and were validated using source and technique triangulation. The findings indicate that character education was implemented through three interconnected strategies: (1) integrating politeness and discipline values into lesson planning, (2) implementing learning activities based on teacher modeling, classroom rules, and habitual use of polite language, and (3) reinforcing moral knowledge, moral feeling, and moral action throughout the learning process. Evidence from classroom observations showed that students generally demonstrated polite language use, compliance with classroom norms, and positive communication during learning activities, while the interviewed student's perspectives complemented these observational findings. The study proposes a conceptual model illustrating how Indonesian Language instruction can support the integration of character education within the school context. These findings provide practical guidance for teachers and school leaders in implementing systematic and integrated character education programs.